1990
DOI: 10.1111/j.1469-8137.1990.tb00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liming on ectomycorrhizal fungi infecting Pinus sylvestris L.

Abstract: summary Growth rates of ectomycorrhizal fungi were measured in pure culture at pH 3–8 on MMN‐agar and sterilized peat, with and without nutrients added. Mycorrhizas were synthesized with Pinus sylvestris L. seedlings and the growth rate of the external mycelium was measured in peat at pH 3.8 and 7.3. The fungi were three isolates of Piloderma croceum Erikss. & Hjorts., two isolates of an unidentified (pink) mycorrhizal type and one isolate of another unidentified (white long) mycorrhizal type, all isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 22 publications
(17 reference statements)
2
19
0
Order By: Relevance
“…P. fallax is characterized by a low growing mycelium highly sensitive to temperature (Erland and Finlay, 1992). Mycelium extension is increased when the fungus is connected with host plants (Erland et al, 1990), and Dahlberg and Stenströ m (1991) demonstrated connections with mature host plants to be important for efficient colonization of young seedlings.…”
Section: Systematic Biology and Ecologymentioning
confidence: 99%
“…P. fallax is characterized by a low growing mycelium highly sensitive to temperature (Erland and Finlay, 1992). Mycelium extension is increased when the fungus is connected with host plants (Erland et al, 1990), and Dahlberg and Stenströ m (1991) demonstrated connections with mature host plants to be important for efficient colonization of young seedlings.…”
Section: Systematic Biology and Ecologymentioning
confidence: 99%
“…Other facvide further information on fungal-root physiology interactors such as the absence of associated microflora, nutrient tions during water stress. An understanding of the mechanisms levels, temperature, soil pH, fungal growth factors, and plant determining intraspecific variability in mycelial strand forroot exudates also affect development of the extramatrical mation, extension of the extramatrical phase, and physiologphase (Bethelenfalvay et al 1988;Coutts and Nicoll 1990; ical response to adverse stress could advance our kncwledge Erland et al 1990;Garbaye and Bowen 1987;McAffee and and enable us to apply biotechnology to reforestation. Fortin 1988; Slankis 1974).…”
Section: Recent Research Conducted Bymentioning
confidence: 98%
“…In general, differences in ECM fungal community composition have been observed after lime application (Andersson and Söderström 1995;Erland and Taylor 2002;Kjøller and Clemmensen 2009). ECM fungal mycelium was shown to grow slower in limed peat substrate with increased pH than in unlimed peat (Erland et al 1990). Wood ash and lime are rather similar in their buffering capacity, but wood ash contains larger amounts of K, Mg, Mn, Na and P as well as toxic heavy metals (Augusto et al 2008).…”
Section: Introductionmentioning
confidence: 98%